Influence Of The Skin Structure Of Wax Apple (Syzygium samarangense) Varities On Post Harvest Handling. - Siti Syahidah Binti Nor Ayob (FASM, Universiti Malaysia Terengganu, 2010)
Study on the skin of the fruit of wax apple, Syzygium samarangense, was executed by using Scanning Electron Microscope (SEM) to see the microstructur on surface and the cross section of the fruit and compare it by using Microtome and Toluidine Blue to get a clear structure to the skin of the fruit of wax apple. The tissues of skin of wax apple were used in counting stomata which affect the fruit quality in addition influenced by the environment and post harvest handling. In addition, there was the wax apple tissues that were used for Scanning Electron Microscope (SEM) and also the histology part to obtain high quality images of skin structure and more clearly. Through this study, the post harvest handling affect the quality of the fruit especially the skin and if the fruit are not correctly handled it will cause damage to the fruit because the skin of wax apple is very thin and require a good handling.